Mariposas bioindicadoras ecológicas en México. Artículo de revisión - Orta S., Carolina; Reyes-Agüero, Juan Antonio; Luis-Martínez, Moisés Armando; Muñoz-Robles, Carlos Alfonso; Méndez C., Heriberto (Instituto de Ecología, A.C., 2022)
About 1,900 species of the superfamily Papilionoidea have been described in Mexico (sensu lato), which includes all diurnal lepidoptera in the country (Llorente-Bousquets et al., 2014). Diurnal butterflies are recognized as a widely studied taxon and can be used as ecological bioindicators. This review article compiles information on this subject in Mexico, identifying 58 articles and research papers that mention indicator species, although only 16 of them use statistical methods, mostly multivariate, to identify them as ecological bioindicators. Information on 179 bioindicator butterfly’s species was compiled in annexes, highlighting the main characteristics that facilitate their research in the field, such as vegetation type, feeding habits, phenology, and specialization degree. Of the 179 bioindicator species, 55 were recorded in conserved areas, 99 in disturbed areas and 25 in both conditions, although from different studies and in different habitats. In addition, a list of host plants in the country is annexed for 116 species of the 179 identified to facilitate their association with the respective plant community and their interactions. Finally, recommendations are made for a sampling design that would allow the use of these bioindicator species as an object of study in medium-term environmental monitoring projects.